2018
DOI: 10.1039/c8ta03857k
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the performance of organic cathodes through structure tuning

Abstract: Two novel redox-active organic cathodes PPTO and PEPTO have been developed. The replacement of a single C–C bond (in PPTO) with a carbon–carbon (CC) triple bond (in PEPTO) could greatly enhance the performance of organic cathodes. As a result, PEPTO delivers a significantly improved rate stability at high current densities and an excellent capacity retention of 110 mA h g−1 after 1000 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 55 publications
0
93
0
Order By: Relevance
“…Notably,the introduction of an ethynyl moiety into the backbone led to asignificantly improved rate capability. [49] Two-dimensional covalent organic frameworks (COFs) containing redox-active quinone moieties were presented by Wu et al, [50b] AbruÇae tal., [50c] and Wang et al [50a] Applyinge xfoliated few-layer nanosheets of the COFs in combination with al ithium counter electrode, ac ell featuring ad ischarge voltage of 2.8 Va nd ac apacity that is stable over 1000 cycles was demonstrated ( Figure 5). [50a]…”
Section: Batterys Ystem Vmentioning
confidence: 99%
“…Notably,the introduction of an ethynyl moiety into the backbone led to asignificantly improved rate capability. [49] Two-dimensional covalent organic frameworks (COFs) containing redox-active quinone moieties were presented by Wu et al, [50b] AbruÇae tal., [50c] and Wang et al [50a] Applyinge xfoliated few-layer nanosheets of the COFs in combination with al ithium counter electrode, ac ell featuring ad ischarge voltage of 2.8 Va nd ac apacity that is stable over 1000 cycles was demonstrated ( Figure 5). [50a]…”
Section: Batterys Ystem Vmentioning
confidence: 99%
“…With the depletion of fossil fuels and ever‐increasing energy demands as well as adverse greenhouse effect, the efficient utilization of renewable power sources (e.g., wind, wave, solar) has become the most significant issue that must be confronted. [ 1–4 ] However, the intermittent characteristic of these renewable energy sources indicates that they cannot be used directly. Such a problem urgently requires scientists to pursue efficient energy‐converting devices and reliable energy‐storage systems with high specific energy, long lifespan, and excellent safety.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this issue, many approaches have been attempted, [ 8,9 ] and it is found that rational molecular structure design plays important roles in improving its performance. [ 7,10–21 ] In fact, to reduce the solubility of organic molecules, the key is to strengthen intermolecular interaction. The simplest way is to introduce substituent(s) into BQ to increase the intermolecular van der Waals force or ion interaction (Figure S1a, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%